A Trp-BODIPY cyclic peptide for fluorescence labelling of apoptotic bodies. Issue 5 (23rd December 2016) - Subiros-Funosas, Ramon; Mendive-Tapia, Lorena; Sot, Jesus; Pound, John D.; Barth, Nicole; Varela, Yaiza; Goñi, Felix M.; Paterson, Margaret; Gregory, Christopher D.; Albericio, Fernando; Dransfield, Ian; Lavilla, Rodolfo; et al.
Abstract : We describe the synthesis and characterization of a Trp-BODIPY fluorogenic peptide for labelling subcellular bodies released by human apoptotic cells. Abstract : The rational design and synthesis of a Trp-BODIPY cyclic peptide for the fluorescent labelling of apoptotic bodies is described. Affinity assays, confocal microscopy and flow cytometry analysis confirmed the binding of the peptide to negatively-charged phospholipids associated with apoptosis, and its applicability for the detection and characterisation of subcellular structures released by apoptotic cells.